Assessing the insight of Muslim account holders’ in conventional bank to purchase Islamic Bank products / Kabiru Jinjiri Ringim and Ibrahim Mohd Yussof - Mohd Yussof, Ibrahim (Faculty of Business and Management, 2014)
This study investigates the insight of Muslim account holders’ in conventional bank to purchase Islamic bank products. The concept Insight was defined in terms of Perception, Awareness and Understanding. Hence, the objectives of this study is to assess the effect of Perception, Awareness and Understanding of Muslim’s account holder’s in conventional bank to purchase Islamic bank products. Perception is operationally defined as the opinion, observation, assessment or experience while, Awareness is viewed as the consciousness, recognition or familiarity. Understanding is referred as the comprehension, grasp or appreciation of Muslim’s account holder. A research framework model and hypotheses concerning the relationships among the variables – Perception, Awareness, and Understanding of Muslim’s Account holder’s in conventional bank to purchase Islamic bank products were posited and tested. Data was collected using hand delivery questionnaire survey approach. Using simple random sampling procedure, three hundred and eighty five (385) respondents both male and female were selected to participate in this study. Factor analysis, Pearson correlation, multiple regression methods of data analysis were utilized for hypotheses testing. The results of the correlation revealed that Perception, Awareness and Understanding are positively associated with Muslim account holders in conventional banks toward Islamic banking products. The multiple regression results indicate that Understanding and Awareness factors jointly explained 27.1% of the variance of Muslim account holder’s in conventional bank toward patronising Islamic bank products. The outcome of this study provides vital information on the effect of Awareness and Understanding of Muslim account holder’s in conventional bank to purchase Islamic banking products. The managerial implication of this study is for the Islamic banking industry to focus on the people’s understanding of Shariah position on business transactions, concept of profit and loss sharing practice, benefit of Islamic banking products, good understanding of Islamic banking theory and practice that would have impact on customer decision.